Do different lipid components accelerate the pathogenesis and severity of Diabetic Retinopathy? - Lakshmi Kanta Mondal; Subhasish Pramanik; Subhankar Chowdhury; Chiranjit Bose; Debgopal Bera; Ayindrila Saha; Koena Bhattacharjee (International Journal of Retina and Vitreous, 2022)
Abstract Background To assess the association of lipid and lipid-derived toxic molecules in pathogenesis and severity of diabetic retinopathy (DR) in type 2 diabetes mellitus (T2DM). Methods The present cross-sectional study included 14 healthy individuals (HC) without T2DM, 22 T2DM subjects without DR (DNR), 24 T2DM subjects with mild non-proliferative DR (MNPDR), and 24 T2DM subjects with high-risk proliferative DR (HRPDR). All subjects underwent plasma and vitreous analysis for estimation of total lipid (TL), free fatty acid (FFA), lipid peroxides (LPOs) like malondialdehyde (MDA), 4-Hydroxy-noneal (HNE), the advanced lipoxidation end product (ALE) like Hexanoyl-lysine (HLY) and vascular endothelial growth factor (VEGF) following standard spectrophotometric and enzyme-linked immunosorbent assay (ELISA) methods respectively. Results The concentration of TL, FFA, markers of lipid peroxidation and lipoxidation as well as VEGF in plasma and vitreous were found to be significantly elevated stepwise inT2DM subjects (HRPDR > MNPDR > DNR) compared to healthy controls (HC).Further, plasma conventional lipid components like total cholesterol (TCH), low density lipoprotein cholesterol (LDL-C) and triglycerides (TG), FFA and TL showed their significant positive correlations with vitreous level of different LPOs, ALE and VEGF in the DR group. Conclusion Total lipid and lipid-derived detrimental biomolecules ultimately result in increased secretion of VEGF and thus not only add as associated mediators in the pathogenesis of DR, these also accelerate the severity of microangiopathy in T2DM.